How Emotional Intelligence and Adversity Quotient Impact Organizational Citizenship Behavior: A Meta-Analysis - Sulistiasih, Sulistiasih; Mardiaty, Netty; Afriyenti, Lenny Utama (Psychocentrum Review, 2024)
Every organization wants to survive and develop. Therefore, extra-role behavior, commonly called organizational citizenship behavior (OCB), is required. OCB is absolutely essential for both personal and organizational dynamics. Hence, the objective of this investigation is to ascertain the impact of emotional intelligence (EI) and adversity quotient (AQ) on OCB. This investigation employs quantitative methodologies grounded in a literature review, which are then subjected to meta-analysis. 16 pertinent articles were selected from Scopus, SINTA, and Google Scholar between 2018 and 2024 to conduct a literature review. Meta-analysis using JASP 0.8 4.0 software found that EI and AQ significantly affected OCB, with a correlation coefficient (r) = 0.373 and 0.337 at p-value < 0.01. EI has a stronger influence on OCB than AQ. In addition, this research does not show publication bias, so the publications reviewed genuinely reflect the actual situation. This evidence confirms and strengthens previous relevant research used as the basis of the meta-analysis and offers new things regarding the influence of EI and AQ that significantly influence OCB. Therefore, the findings deserve further discussion among researchers and practitioners in the future